Effectiveness of Annona muricata L on the Inhibition of Streptococcus mutans - Linda Dwi Safitri; Wahyuni Dyah Parmasari (Universitas Syiah Kuala, 2025)
Streptococcus mutans is widely recognized as the primary etiological agent of dental caries and is a normal inhabitant of dental plaque. The growth of this bacterium may be inhibited by herbal agents, including soursop leaves (Annona muricata L.), which contain bioactive compounds such as saponins, triterpenoids, tannins, alkaloids, flavonoids, and phenolic compounds known for their antibacterial properties. Based on this rationale, the present study aimed to further the inhibitory effect of soursop leaf extract on the growth of Streptococcus mutans. The bacterial isolates used in this study were obtained from the Microbiology Laboratory at the Faculty of Medicine, Wijaya Kusuma University, Surabaya. A minimum of four samples were included in each of six treatment groups with extract concentrations of 15 mg/mL, 30 mg/mL, 40 mg/mL, 45 mg/mL, 50 mg/mL, and 60 mg/mL. One negative control group received sterile distilled water, while one positive control group was treated with amoxicillin without soursop leaf extract. Samples were assigned using a simple random sampling technique. Data were analyzed using Analysis of Variance (ANOVA). The results indicated that a concentration of 15 mg/mL of soursop leaf extract (Annona muricata L.) effectively inhibited the growth of Streptococcus mutans